2019
DOI: 10.1002/ajs4.84
|View full text |Cite
|
Sign up to set email alerts
|

“Moved on”? An exploratory study of the Cashless Debit Card and Indigenous mobility

Abstract: What is the relationship between the first two trials of the Cashless Debit Card (CDC) and Indigenous mobility? In Ceduna, Vincent conducted ethnographic research into lived experiences of the first CDC trial. In the East Kimberley, Klein conducted 51 structured interviews with people on the card and 37 semi‐structured interviews with key informants. Markham used regression analysis of net migration rates at the Statistical Area 2 level to determine whether the CDC trial sites were associated with greater net … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Furthermore, poorly understood local realities, which include unreliable and slow Internet connectivity, result in high levels of non-compliance recorded in the system, which reinforced political narratives of Indigenous dysfunction as well as impacting on Indigenous people's payments, food security and well-being (see Jordan & Fowkes 2016). Vincent et al (2019) turn their attention to a somewhat neglected issue: the nexus between welfare conditionality and mobility (but see Marston et al 2019). They provide a tentative exploration of a possible relationship between increased mobility in the East Kimberley and Ceduna and the first two trials of the Cashless Debit Card.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, poorly understood local realities, which include unreliable and slow Internet connectivity, result in high levels of non-compliance recorded in the system, which reinforced political narratives of Indigenous dysfunction as well as impacting on Indigenous people's payments, food security and well-being (see Jordan & Fowkes 2016). Vincent et al (2019) turn their attention to a somewhat neglected issue: the nexus between welfare conditionality and mobility (but see Marston et al 2019). They provide a tentative exploration of a possible relationship between increased mobility in the East Kimberley and Ceduna and the first two trials of the Cashless Debit Card.…”
mentioning
confidence: 99%
“…Vincent et al () turn their attention to a somewhat neglected issue: the nexus between welfare conditionality and mobility (but see Marston et al ). They provide a tentative exploration of a possible relationship between increased mobility in the East Kimberley and Ceduna and the first two trials of the Cashless Debit Card.…”
mentioning
confidence: 99%
“…Indigenous youth, like any other group, play a significant role in shaping the future of society, and their perspectives and preferences should be taken into account when considering the adoption of cashless payments. A previous study draws attention to the relationship between welfare payments, other forms of remote service delivery, and questions of mobility and immobility (Vincent et al, 2020). The study identified a concept of "orbiting" emerged and it is fostering disempowerment, passivity and social pathologies of reduced dependence on "welfare poison", thus it was minimally elaborated (Burke, 2013).…”
Section: Cashless Society Among Indigenous Youthmentioning
confidence: 99%
“…Notably, the introduction of the Centrelink debit card system in Ceduna (Vincent, Markham et al 2020) was seen as a contributor to homelessness in the area, with people using a non-Ceduna (i.e. Davenport) address so they could receive their payments in the usual way.…”
Section: ) Persons Who Are Marginally Housed Includes Persons Living ...mentioning
confidence: 99%